Controlled growth of large-sized and phase-selectivity 2D GaTe crystals - Liu, Mingqiang (2022)
GaTe has recently attracted significant interest due to its direct bandgap and unique phase structure, which makes it a good candidate for optoelectronics. However, the controllable growth of large-sized monolayer and few-layer GaTe with tunable phase structures remains a great challenge. Here the controlled growth of large-sized GaTe with high quality, chemical uniformity, and good reproducibility is achieved through liquid-metal-assisted chemical vapor deposition method. By using liquid Ga, the rapid growth of 2D GaTe flakes with high phase-selectivity can be obtained due to its reduced reaction temperature. In addition, the method is used to synthesize many Ga-based 2D materials and their alloys, showing good universality. Raman spectra suggest that the as-grown GaTe own a relatively weak van der Waals interaction, where monoclinic GaTe displays highly-anisotropic optical properties. Furthermore, a p-n junction photodetector is fabricated using GaTe as a p-type semiconductor and 2D MoSe2 as a typical n-type semiconductor. The GaTe/MoSe2 heterostructure photodetector exhibits large photoresponsivity of 671.52 A W-1 and high photo-detectivity of 1.48 × 1010 Jones under illumination, owing to the enhanced light absorption and good quality of as-grown GaTe. These results indicate that 2D GaTe is a promising candidate for electronic and photoelectronic devices.